The patatin-containing phospholipase A pPLAIIα modulates oxylipin formation and water loss in Arabidopsis thaliana - Yang, Wenyu; Zheng, Yong; Bahn, Sung Chul; Pan, Xiangqing; Li, Maoyin; Vu, Hieu Sy; Roth, Mary R.; Scheu, Brad; Welti, Ruth; Wang, Xuemin (My University, 2012)
The patatin-related phospholipase A (pPLA) hydrolyzes membrane glycerolipids to produce monoacyl compounds and free fatty acids. Phospholipids are cleaved by pPLAIIα at the sn-1 and sn-2 positions, and galactolipids, including those containing oxophytodienoic acids, can also serve as substrates. Ablation of pPLAIIα decreased lysophosphatidylcholine and lysophosphatidylethanolamine levels, but increased free linolenic acid. pPLAIIα-deficient plants displayed a higher level of jasmonic acid and methyl jasmonate, as well as the oxylipin-biosynthetic intermediates 13-hydroperoxylinolenic acid and 12-oxophytodienoic acid than wild-type plants. The expression of genes involved in oxylipin production was also higher in the pPLAIIα-deficient mutant than in wild-type plants. The mutant plants lost water faster than wild type plants did. The stomata of wild type and mutant plants responded similarly to abscisic acid. In response to desiccation, the mutant and wild type leaves produced abscisic acid at the same rate, but after 4 h of desiccation, the jasmonic acid level was much higher in mutant than wild-type leaves. These results indicate that pPLAIIα negatively regulates oxylipin production and suggest a role in the removal of oxidatively modified fatty acids from membranes.
Keywords: Patatin-related phospholipase A; Oxidative modified lipids; Jasmonate synthesis; Water loss; Arabidopsis thaliana